Measurement of the total and differential Higgs boson production cross-sections at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector by combining the H → ZZ * → 4ℓ and H → γγ decay channels. (Tufts University. Tisch Library., 2023)
Keywords : Hadron-Hadron Scattering, Higgs Physics.; Springer Open.